KINERJA PEGAWAI PADA KANTOR PRIMER KOPERASI KEPOLISIAN RESORT BIMA KOTA - Sari Lukman, Dwi Ratna Kamala (Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram, 2019)
Performance is an achievement produced by employees in an organization. Employee performance is a benchmark in determining an organization can develop and experience improvement. This study aims to determine the ability of employees to improve performance at the Primary Cooperative Office of the Bima City Police Department. This type of research is descriptive. Data collection techniques using purposive sampling include: interviews, documentation, and observation. Interviews were conducted on several informants, namely Management, Employees, Supervisory Board of the Head of the Savings and Loan Unit and Members of the Cooperative Primary Office of the Bima Kota Police Department. The data analysis technique in this study is qualitative, starting with data reduction, data presentation and data withdrawal. The results of this study indicate that the ability of employees to improve performance at the Cooperative Primary Office of the Bima City Resort Police has strongly supported the development of cooperative business activities, both in terms of aspects: ability and expertise in completing assignments on time, employee skills in carrying out tasks, and educational background or the knowledge possessed by employees in completing work and efforts to improve the performance of employees with training and incentives has been implemented well even though it still needs to further improve employee performance in order to increase yields that exceed the target at the Bima Koperasi Resort Primary City Office.